An over 10% module efficiency obtained using non-Bi2Te3 thermoelectric materials for recovering heat of <600 K. Issue 12 (10th November 2021) - Bu, Zhonglin; Zhang, Xinyue; Hu, Yixin; Chen, Zhiwei; Lin, Siqi; Li, Wen; Pei, Yanzhong
Abstract : This work illustrates the existence of thermoelectric materials and devices other than the historical Bi2 Te3 -based ones for efficiently generating electricity from extremely abundant, low-grade waste heat of <600 K. Abstract : Thermoelectric technology offers the unique advantages of being completely solid-state, silent and emission-free for waste-heat recovery applications. Despite this, existing thermoelectric modules, particularly for recovering low-grade but abundant heat of <600 K, have been limited to Bi2 Te3 alloys in both p- and n-type conductors for more than half a century. These Bi2 Te3 -based modules have remained stagnant with a poor efficiency of <7%. Recently developed p-GeTe and n-Mg3 Sb2 have shown great potential in competing with the performance of historical Bi2 Te3 thermoelectrics, realizing efficient thermoelectric applications while creatively using non-Bi2 Te3 materials. In this work, we demonstrated a module-level conversion efficiency of >10% with a heat source temperature of <600 K using p-GeTe/n-Mg3 SbBi thermoelectrics. This was enabled by the extraordinary thermoelectric performance of both the p- and n-type materials. In addition, a design of Ag/SnTe/GeTe and Ni/Fe/Mg3 SbBi contacts enabled an efficient prevention of chemical diffusion as well as low interfacial resistivity. This work illustrates that non-Bi2 Te3 thermoelectrics have the potential to realize an even higher efficiency in recovering abundant low-grade (<600 K) waste heat.